Dual‐task difficulties as a risk factor for unemployment in people with multiple sclerosis - Turhan Kahraman; Hasretgul Temiz; Zuhal Abasiyanik; Cavid Baba; Serkan Ozakbas (Brain and Behavior, 2023)
Abstract Background No study has investigated the impact of dual‐tasking difficulties as a risk factor for unemployment in people with multiple sclerosis (pwMS). The aim was to examine the influence of dual‐task performance on employment status and work difficulties and to identify the predictors of employment status in pwMS. Methods Eighty‐four pwMS, including 42 employed and 42 unemployed, participated in the study. Dual‐task difficulties were assessed using the Dual‐task Impact on Daily‐living Activities‐Questionnaire (DIDA‐Q), while dual‐task performance was evaluated through the 30‐second Walk Test and Nine‐Hole Peg Test, incorporating a cognitive task. Walking and cognitive function were also measured. Results Employed pwMS had better scores in walking, cognitive function, single and dual‐task performance than unemployed pwMS (p < .05). Lower scores in walking (odds ratio [OR] = 1.81, p < .001) and upper extremity‐related (OR = 1.44, p = .019) dual‐task performance and higher scores in the cognitive subscale of the DIDA‐Q questionnaire (OR = 1.20, p = .037) were significantly associated with higher odds of being unemployed. Among employed pwMS, DIDA‐Q subscales showed moderate‐to‐strong correlations with MSWSDQ‐23 scores. The other variables showed weak‐to‐moderate correlations with subscale and total scores of MSWSDQ‐23. Conclusion Cognitive function, as opposed to motor function, has been found to be a significant predictor of unemployment in pwMS.